110k views
3 votes
Rearrange the equation below to solve for y.
4y - 3a = 13a

User Javsmo
by
5.3k points

2 Answers

4 votes
Hi there!

The rearranged equation solving for y is “y = 4a”

Move all the terms not containing the y to the right side of the equation.

4y = 16a

Then divide both sides by 4!

Hope this helps!
User Harinsamaranayake
by
5.5k points
1 vote

Answer:


\boxed{\huge {\sf y = 4a}}

Explanation:


\sf Solve \: for \: y: \\ \sf \implies 4y - 3a = 13a \\ \\ \sf Add \: 3a \: to \: both \: sides: \\ \sf \implies 4y + ( \boxed{ \sf 3a} - 3a) = \boxed{ \sf 3a} + 13a \\ \\ \sf 3a - 3a = 0 : \\ \sf \implies 4y = 3a + 13a \\ \\ \sf 3a + 13a = 16a : \\ \sf \implies 4y = 16a \\ \\ \sf Divide \: both \: sides \: by \: 4: \\ \sf \implies \frac{4y}{ \boxed{ \sf 4}} = \frac{16a}{ \boxed{ \sf 4}} \\ \\ \sf (4y)/(4) = \frac{ \cancel{ \sf 4}}{\cancel{ \sf 4}} * y = y : \\ \sf \implies y = (16a)/(4) \\ \\ \sf (16a)/(4) = \frac{\cancel{ \sf 4} * 4a}{\cancel{ \sf 4}} = 4a : \\ \sf \implies y = 4a

User Kathiria
by
4.4k points